PENGARUH KONDISI SOSIAL DAN PENDAPATAN ORANG TUA TERHADAP TINGKAT PENDIDIKAN ANAK DI DESA PULAU KEDUNDUNG KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - pratiwi, Mailander Ayu; Indrawati, Henny; Johan, Rina Selva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted at the Kedundung Island Central District of Kuantan District Kuantan Singingi with the aim to analyze the influence of the Social Condition and Income Education Level Parents to Children. The population in this study were 262 head of the family and samples in this study is the parents who have school age children 7-18 years using cluster random sampling technique using Slovin formula that produced 73 samples. Data was collected through questionnaire techniques while data is primary data and secondary data. Furthermore, the data were analyzed using multiple regression analysis, the coefficient of determination, simultaneous test (F test) and partial test (t test). There are two variables: social conditions and income, but in research variables social conditions are translated into a number of variables including the level of education of the father (X1), level of education mother (X2), father age (X3), and mother age (X4) and the second variable income people old (X5). The results showed that the father's education level variables, mother's educational level, father age, mother age and income of parents simultaneously influence the level of education of children, as is evident from the test results Fhitung greater than Ftable. This means that independent variables jointly affect the dependent variable. Furthermore, based on partial test (t test) it can be seen that only the father's education level variables that affect child's education level indicated  the significance of 0.003 while the other variables have no effect.To every parent is expected to pay attention to their children's education because children who have the education usually have more advanced mindset in order for the welfare of the family and the parents are very decisive role in making decisions for the school children Keywords: Social Conditions, Income Parents, Level of Education.